The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1351/pac199264050715
|View full text |Cite
|
Sign up to set email alerts
|

Plasma polymerization and surface treatment of polymers

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
1
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 1 publication
0
62
1
4
Order By: Relevance
“…4,5,13 Weikart and Yasuda 13 reported that plasma-induced surface damage of polymers resulted in the formation of a certain amount of low-molecular-weight oligomers which were washed away after immersion in water. To compare the effects of LTCAT treatments, in this study RF plasma treatments of LDPE were investigated by varying plasma exposure time, while keeping RF power, system pressure, and flow rate fixed.…”
Section: Rf Plasma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5,13 Weikart and Yasuda 13 reported that plasma-induced surface damage of polymers resulted in the formation of a certain amount of low-molecular-weight oligomers which were washed away after immersion in water. To compare the effects of LTCAT treatments, in this study RF plasma treatments of LDPE were investigated by varying plasma exposure time, while keeping RF power, system pressure, and flow rate fixed.…”
Section: Rf Plasma Treatmentmentioning
confidence: 99%
“…Ample data indicate that this "uncontrollable" plasma treatment can bring about many undesirable changes in and damage to the surface of polymers, such as degradation of polymer chains and etching of the surface materials. 4,5 These undesirable changes and damage of polymer surfaces have many detrimental effects on their applications, such as loss of wettability, adhesion failure from weak-boundary-layer (WBL) formation, and loss of tensile strength of polyethylene fibers resulting from plasma etching. 6,7 If a desirable surface modification is accomplished at the expense of degradation of the substrate, the value of such a modification is questionable.…”
Section: Introductionmentioning
confidence: 99%
“…As plasma polymers are derived from the assembly of various molecular fragments produced in the plasma vapour phase, their chemical structure tends to be random and more cross-linked compared to conventional polymers [3]. Moreover, plasma-polymerised films are generally amorphous, free from pinholes, highly resistant to heat and corrosion and very adhesive to a variety of substrates including conventional polymer, glass and metal surfaces [6][7][8]. Owing to these excellent characteristics, plasma polymers have been used in a wide variety of applications including barrier coatings, protective coatings, selective permeation membranes, dielectric layers in microelectronics, … [9].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma polymerization process refers to formation of thin polymer films by fragmentation of organic compounds into radicals and their recombination during film growth [3][4][5][6]. Due to the unique properties such as good adhesion to substrates, highly cross-linked layers and controlled thickness at nanoscale [7] the plasma polymerized films are becoming increasingly important for a wide range of applications, from functional coatings for biomolecules immobilization [8] to dielectric materials in microelectronics and nanoelectronics.…”
Section: Introductionmentioning
confidence: 99%